Bacterial pathogens of the lower respiratory tract of calves from Brazilian rural settlement herds and their association with clinical signs of bovine respiratory disease - Natália C. Gaeta; Bruno L.M. Ribeiro; Mario A.R. Alemán; Eidi Yoshihara; Alessandra F.C. Nassar; Lucas M. Marques; Jorge Timenetsky; Lilian Gregory (Pesquisa Veterinária Brasileira)
ABSTRACT: Bovine respiratory disease (BRD) is considered the major cause of economic losses in dairy and beef cattle production. The study aimed to detect the most important bacteria related to respiratory disease in tracheobronchial fluid samples of healthy and dairy calves with clinical signs of BRD in Brazilian rural settlements. Hundred and forty-one mongrel dairy calves were randomly selected from 42 family farm dairy herds from Brazilian settlements. Physical examination was performed and calves were classified as healthy (n=100) and BRD (n=41). Tracheobronchial fluid samples were collected. Isolation and molecular detection of Mycoplasma dispar, M. bovis and M. mycoides subsp. mycoides SC besides isolation of other aerobic bacteria were performed. Abnormal lung sounds (crackle/snoring/whistle), mucopurulent/purulent nasal discharge, body temperature >39.5°C and respiratory rate >40 breaths/min were higher in BRD calves compared to healthy calves (P<0.05). Bacillus sp., Staphylococcus intermedius and non-fermentative Gram-negative were the most prevalent bacteria isolated. Non-identified species from Enterobacteriaceae family was higher in BRD calves compared to healthy calves (P<0.05). Mollicutes were isolated in 7.4% of samples and only M. dispar was detected. Mollicutes was associated with purulent/mucopurulent nasal discharge (P=0.017). Pantoea agglomerans was associated to tachypnea (P=0.020), and Streptococcus spp. was associated with hyperthermia. Statistical tendencies were observed to M. dispar and tachypnea (P=0.066), and P. agglomerans and tachycardia (P=0.066). The obtained results describe the microorganisms found in tracheobronchial fluid of calves with BRD in some herds of Brazilian family farming and their relation to clinical signs of BRD.